(3GdYed HGdCSWQdGHs
(3ChdgG (B:s
(3hGdMeO ddg GdPi jSJMb GdMeO dYRJg hHYO agPG eNJUQ eTJed Ydi fHPI ai GdYed HGdCSWQdGH GdChd ai CSGei BdGJ GdCSWQdGH s
(3BNQgG (B:s
(3GdHGH GdKGef YTQ (B: (3ai eYQaI GdSeJ dcd GQJaGY ddeTS hGdchGcH aeG cGf JMJgG ef CLRGA GdSehJ agh SeJ Pdc GdGQJaGY Je s
(3Vef eLehY , JQJjHgG (B: (3ef U (B110 - (3U(B113s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJjcGf (B(494) s
Keywords: (3Gdadcs